Test Your English Vocabulary in Use: Upper - intermidiate - McCarthy, Michael (Cambridge University, 2001)
This book provides a series of tests on different aspects of English vocabulary at an upper-intermidiate level. It is based on the vocabulary presented and practised in the units of English Vocabulary in Use: upper-intermidiate. There are references in the contents pages and in each test to show you which units or units each test is based on. In a few cases vocabulary in use and, when this happens, the instructions for the excercise suggest that you may use a dictionary if you wish. You can, of course, use these tests even if you have not been working with English Vocabulary in Use but are simply interested in assessing your knowledge of the vocabulary area coverted by the test.